Tissue-specific human beta-defensins (HBD)-1, HBD-2 and HBD-3 secretion profile from human amniochorionic membranes stimulated with Candida albicans in a two-compartment tissue culture system - Zaga-Clavellina Veronica; Ruiz Martha; Flores-Espinosa Pilar; Vega-Sanchez Rodrigo; Flores-Pliego Arturo; Estrada-Gutierrez Guadalupe; Sosa-Gonzalez Irma; Morales-Méndez Iyari; Osorio-Caballero Mauricio (BMC, 2012)
Abstract Background During intrauterine infection, amniochorionic membranes represent a mechanical and immunological barrier against dissemination of infection. Human beta defensins (HBD)-1, HBD-2, and HBD-3 are key elements of innate immunity that represent the first line of defense against different pathogen microorganisms associated with preterm labor. The aim of this work was to characterize the individual contribution of the amnion (AMN) and choriodecidua (CHD) regions to the secretion of HBD-1, HBD-2 and HBD-3, after stimulation with Candida albicans. Methods Full-thickness human amniochorionic membranes were obtained after delivery by elective cesarean section from women at 37-40 wk of gestation with no evidence of active labor. The membranes were cultured in a two-compartment experimental model in which the upper compartment is delimited by the amnion and the lower chamber by the choriodecidual membrane. One million of Candida albicans were added to either the AMN or the CHD face or to both and compartmentalized secretion profiles of HBD-1, HBD-2, and HBD-3 were quantified by ELISA. Tissue immunolocalization was performed to detect the presence of HBD-1, -2, -3 in tissue sections stimulated with Candida albicans. Results HBD-1 secretion level by the CHD compartment increased 2.6 times (27.30 [20.9-38.25] pg/micrograms protein) when the stimulus with Candida albicans was applied only on this side of the membrane and 2.4 times (26.55 [19.4-42.5] pg/micrograms protein) when applied to both compartments simultaneously. HBD-1 in the amniotic compartment remained without significant changes. HBD-2 secretion level increased significantly in the CHD when the stimulus was applied only to this region (2.49 [1.49-2.95] pg/micrograms protein) and simultaneously to both compartments (2.14 [1.67- 2.91] pg/micrograms protein). When the stimulus was done in the amniotic compartment HBD-2 remained without significant changes in both compartments. HBD-3 remained without significant changes in both compartments regardless of the stimulation modality. Localization of immune-reactive forms of HBD-1, HBD-2, and HBD-3 was carried out by immunohistochemistry confirming the cellular origin of these peptides. Conclusion Selective stimulation of amniochorionic membranes with Candida albicans resulted in tissue-specific secretion of HBD-1 and HBD-2, mainly in the CHD, which is the first region to become infected during an ascending infection.